Carbon‐Coated Li3N Nanofibers for Advanced Hydrogen Storage. (21st August 2013) - Xia, Guanglin; Li, Dan; Chen, Xiaowei; Tan, Yingbin; Tang, Ziwei; Guo, Zaiping; Liu, Huakun; Liu, Zongwen; Yu, Xuebin
<x xml:space="preserve">Abstract</x> 3D porous carbon‐coated Li3N nanofibers are successfully fabricated via the electrospinning technique. The as‐prepared nanofibers exhibit a highly improved hydrogen‐sorption performance in terms of both thermodynamics and kinetics. More interestingly, a stable regeneration can be achieved due to the unique structure of the nanofibers, over 10 cycles of H2 sorption at a temperature as low as 250 °C. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>